Albuterol combined with tiotropium bromide to improve the conditions and pulmonary functions of patients with acute exacerbation of chronic obstructive pulmonary disease. Issue 1 (1st January 2020) - Jiang, Zhendong; Huang, Youming; Jiang, Hui; Wang, Ping; Zhang, Lei; Ren, Li; Han, Ping
Abstract : We aimed to explore the clinical efficacy and effects of albuterol combined with tiotropium bromide on pulmonary functions of patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD). 72 patients with AECOPD were divided into a combination treatment group ( n = 38, albuterol + tiotropium bromide) and the control group ( n = 34, routine treatment). Efficacy, incidence of adverse reactions, results of blood gas analysis, pulmonary function indices, time to improve clinical symptoms, St. George's respiratory questionnaire (SGRQ), and British Medical Research Council (MMRC) scores were compared between the two groups. The overall response rate was significantly higher, and the time to improve coughing was significantly shorter, in the combination treatment group compared with controls ( p < 0.05). After treatment, both groups achieved a marked rise in PaO2, forced expiratory volume in 1 s (FEV1), FEV1/forced vital capacity (FVC) ratio, and peak expiratory flow (PEF) ( p < 0.05), which was more dominant with combination therapy. The reduction in PaCO2 was more obvious in the combination therapy group. The combination of albuterol and tiotropium bromide is an effective treatment for patients with AECOPD and functions by improving conditions and pulmonary functions without raising the incidence of adverse reactions.